Molecular Basis for Auto- and Hetero-catalytic Maturation of a Thermostable Subtilase from Thermophilic Bacillus sp. WF146 - Zhu, Hui (American Society for Biochemistry and Molecular Biology, 2013)
The proform of the WF146 protease, an extracellular subtilase produced by thermophilic Bacillus sp. WF146, matures efficiently at high temperatures. Here we report that the proform, which contains an N-terminal propeptide composed of a core domain (N*) and a linker peptide, is intrinsically able to mature via multiple pathways. One autocatalytic pathway is initiated by cis-processing of N* to generate an autoprocessed complex N*-I(WT), and this step is followed by truncation of the linker peptide and degradation of N*. Another autocatalytic pathway is initiated by trans-processing of the linker peptide followed by degradation of N*. Unlike most reported subtilases, the maturation of the WF146 protease occurs not only autocatalytically but also hetero-catalytically whereby heterogeneous proteases accelerate the maturation of the WF146 protease via trans-processing of the proform and N*-I(WT). Although N* acts as an intramolecular chaperone and an inhibitor of the mature enzyme, the linker peptide is susceptible to proteolysis, allowing the trans-processing reaction to occur auto- and hetero-catalytically. These studies also demonstrate that the WF146 protease undergoes subtle structural adjustments during the maturation process and that the binding of Ca(2+) is required for routing the proform to mature properly at high temperatures. Interestingly, under Ca(2+)-free conditions, the proform is cis-processed into a unique propeptide-intermediate complex (N*-I(E)) capable of re-synthesis of the proform. Based on the basic catalytic principle of serine proteases and these experimental results, a mechanism for the cis-processing/re-synthesis equilibrium of the proform and the role of the linker peptide in regulation of this equilibrium has been proposed.